Cooperative Transition-Metal and Chiral Brønsted Acid Catalysis: Enantioselective Hydrogenation of Imines To Form Amines - Zhou, Shaolin; Fleischer, Steffen; Junge, Kathrin; Beller, Matthias (Angewandte Chemie International Edition, 2011)
Control with an iron hand: A broad range of ketimines underwent enantioselective hydrogenation in the presence of a chiral Brønsted catalyst and a well‐defined nonchiral iron catalyst (see scheme). This procedure constitutes an attractive and environmentally favorable alternative to well‐established asymmetric hydrogenation reactions with precious‐metal catalysts.